Development of E-Book-Based Arabic Teaching Materials - Levan's, Olivia; Oktavia, Nur Afni (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study aims to develop a learning product in the form of media in the form of e-book-based teaching materials for Arabic subjects. Through this e-book, students can learn according to the times which are the main needs in today's world of education. The method used by the researcher in this research is the Research and Development (R & D) method, where the ultimate goal is to produce a product for the research site chosen by the researcher and to be able to test the effectiveness of the product. The lack of student interest in learning Arabic causes the student's grades to not reach the agreed target. Researchers hope that the existence of learning products in the form of interactive e-book-based teaching materials can increase students' enthusiasm for learning Arabic. So that students can increase their interest in learning, especially in learning Arabic through the e-book. So, it can be concluded that the learning product in the form of media containing teaching materials can increase the enthusiasm and effectiveness of students in learning, especially in learning Arabic.